Advanced characterization of by-product carbon film obtained by thermal chemical vapor deposition during CNT manufacturing - Trompeta Aikaterini-Flora A.; Koumoulos Elias P.; Kartsonakis Ioannis A.; Charitidis Costas A. (Manufacturing Review, 2017)
This study is focused on the investigation of the morphology and the characteristics of carbon films, obtained by thermal chemical vapor deposition (T-CVD) on different substrates, during carbon nanotubes (CNTs) manufacturing. These films were examined, by means of optical and electronic microscopy, X-ray photoelectron spectroscopy and Raman spectroscopy. Additional measurements were conducted related with the estimation of their nanomechanical properties. The topography is studied, in combination with the assessment of their mechanical behavior at nanoscale. Through nanoindentation, hardness and elastic modulus together with wear resistance index (H/E) were evaluated. According to this study, it may be remarked that the obtained film is classified as an amorphous carbon film.